Effect of Petroleum Contamination on Soil Properties and the Removal Efficiency of Volatile Organic Compounds Using Air-Stripping System - Stephen YAKUBU; Baba MAKUN (FUDMA Journal of Engineering and Technology, 2026)
A pilot-scale research study was investigated using soil column air stripping (SCAS) system to deal with petroleum contaminants with high concentration of volatile organic chemicals (VOCs) generated in the petroleum production and refining process, and the impacts of stripping temperature and gas-solid volume ratio on the maximum recovery of VOCs were investigated by a bench air stripping experiments, MATLAB programming and comparison with literature data’. This research compared air stripping results with theoretical models implemented in MATLAB, examining the interactive effects of air-to-soil ratio and temperature on the removal efficiency of VOCs through the use of a stripping facility called soil column air stripper. Various analyses were performed to assess how the air-to-soil ratio and temperature influence VOC removal efficiency. Increasing the air-to-soil ratio from 2.4 L/min to 12 L/min improved VOC recovery efficiency, rising from 30.46% to 47.10% after one hour of venting. The VOCs recovery efficiency was attained at 47.85% after approximately 1.5 hours at 12 L/min with unheated air. The use of unheated air at 24°C showed limited effectiveness in VOCs removal, with elimination rates significantly influenced by temperature; at 45°C, recovery efficiency increased from 33.82% to 66.03% after two hours of air stripping. The MATLAB experimental model indicated an increase in mass transfer coefficient from 0.170 × 10⁻⁵ to 0.198 × 10⁻⁵ s⁻¹ corresponding to temperature increasing from 24°C to 45°C respectively. The Henry’s law constant increased from 238.59 to 893.36 atm with the same corresponding temperature rise. Over 99% of VOCs removal efficiencies were obtained for all combinations of temperature and air-to-soil ratio. The findings from air stripping approach showed stripping of VOCs from petroleum contaminated soil can be influence by temperature and air-to-soil ratio while MATLAB experimental model underscored air-to-soil ratio between 2.4 and 21.6 as the most efficient operating point at temperature 20 OC to 50 OC. This showed the effectiveness and accuracy of MATLAB programming over air stripping experiment with an advantage over the conventional method used in literature. The model demonstrated excellent fit and accuracy, evidenced by an R2 of 0.98 and a root mean square error (RMSE) recorded 0.001. ANOVA variance results further validated the statistical significance of the model, with the predicted values all align closely with the experimental data. The results indicated that VOCs removal efficiency dependent on temperature with air-to-soil ratio but other soil factors may have a significant challenge in the practical application of preheated air.